Cost Analysis of The Construction Project for the Malaka Regency Office Building Using the Critical Path Method (CPM) - Thomas Aquino Seki; Andi Patriadi; Sajiyo Sajiyo (Syntax Corporation Indonesia, 2025)
Efficient construction project management is crucial to ensure quality and timely completion within budget constraints, especially for large-scale infrastructure projects. This study examines the application of the Critical Path Method (CPM) in accelerating the construction schedule of the Malaka Regency Regent's Office. The project faced various challenges, including frequent delays caused by design changes, unpredictable weather conditions, labor shortages, and inadequate material or equipment supply. These challenges often disrupted the progress and efficiency of the project, necessitating an effective solution to mitigate potential time and cost overruns. To address these issues and align project progress with the original plan, CPM was utilized to identify critical paths, eliminate lag times, and optimize the overall project schedule. Using CPM analysis and Microsoft Project 2019 software, the project's original duration of 180 calendar days was successfully reduced to 100 calendar days. This acceleration was achieved by streamlining interdependencies between critical activities and optimizing work schedules without increasing project costs. The findings highlight the significant role of CPM in achieving time savings while maintaining the planned budget of IDR 94.59 billion. Moreover, this study demonstrates that proper scheduling, coupled with optimization techniques, can significantly enhance the efficiency and effectiveness of construction projects. These results underscore CPM's potential as a valuable tool for project managers to ensure timely completion without compromising quality or incurring additional costs. This research contributes to the growing body of knowledge in construction project management and offers practical insights for managing similar projects in the future